Pengaruh Ukuran Saringan Dan Suhu Pembakaran Terhadap Membran Keramik Untuk Menyisihkan Zat Organik Dan Warna Pada Air Gambut - Febriansyah, M.; Darmayanti, Lita; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat water has a high concentration of organic substances and is brownish red when consumed directly will have a negative impact on health. Ceramic membrane is a technology that can be used to filter and absorb organic matter and color in peat water. Therefore, this article will present a brief review of making ceramic membrane from clay and rice husk for the remove color and organic matter from peat water. Keywords : ceramic membrane, filtration, peat water